Brain Proteome Changes Induced by Olfactory Learning in Drosophila. - Zhang, Y.; Shan, B.; Boyle, M.; Liu, J.; Liao, L.; Xu, T.; Yates, J.R. (Journal of Proteome Research, 2014)
For more than 30 years, the study of learning and memory in Drosophila melanogaster (fruit fly) has used an olfactory learning paradigm and has resulted in the discovery of many genes involved in memory formation. By varying learning programs, the creation of different memory types can be achieved, from short-term memory formation to long-term. Previous studies in the fruit fly used gene mutation methods to identify genes involved in memory formation. Presumably, memory creation involves a combination of genes, pathways, and neural circuits. To examine memory formation at the protein level, a quantitative proteomic analysis was performed using olfactory learning and 15N-labeled fruit flies. Differences were observed in protein expression and relevant pathways between different learning programs. Our data showed major protein expression changes occurred between short-term memory (STM) and long-lasting memory, and only minor changes were found between long-term memory (LTM) and anesthesia-resistant memory (ARM).